Comparative evaluation of body composition analysis in type-2 diabetes mellitus patients and healthy Nigerians using bioelectric impedance analysis technique - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective:The study was aimed at evaluating the body composition of type-2 diabetes mellitus (T2DM) patients using bioelectric impedance analysis (BIA) technique and comparing their findings with age and sex-matched healthy volunteers.Materials and Methods:One hundred T2DM patients and 100 age and sex-matched controls were recruited in the study. Body composition was measured using BIA system (Tanita BC-554 Tanita Corporation, Tokyo, Japan), the data obtained from the body composition analyser included weight, fat %, fat mass, total body water, muscle mass, basal metabolic rate, bone mass, visceral fat (VF), body mass index and physique rating.Results:A total of 100 T2DM patients, who were matched with 100 of the healthy volunteers by age and sex, comprised 58% males and 42% females in each group. Their mean age was 49 years ± 19 years. The average duration of T2DM was 2.32 ± 0.83 years. The median fat composition was 41.1% in diabetic subjects and 30.5% in control (P= 0.0024). The median body water composition was 45.4% in diabetic subjects and 49.3% in control (P= 0.2106). The median muscle composition was 43.0% in diabetic subjects and 44.7% in control (P= 0.8859). The median physique rate was 4 in diabetic subjects and 2 in control (P= 0.0016). The median basal metabolic rate was 1389 in diabetic subjects and 1430 in control (P= 0.8648). The median metabolic age was 45 in diabetic subjects and 48 in control (P= 0.9143). The median bone component was 2.4 in diabetic subjects and 2.4 in control (P= 0.0922). The median VF component was 12% in diabetic subjects and 6% in control (P= 0.0016).Conclusion:Bioimpedance analyses of body composition showed that T2DM patients have significantly higher body fat, VF and physique rate compared with age and sex-matched healthy controls.